Determination of Patient Satisfaction Through Marketing Strategy and Quality Doctor Services (Study at K-24 Geliting Pharmacy, Maumere) - Sukma, Findwicha Kharisma; H. Purwadhi, H. Purwadhi; Rachman, Arif (Business Management, 2026)
Patient satisfaction is a key indicator in assessing the quality of healthcare services, including in pharmaceutical service facilities such as Apotek K-24 Geliting Maumere. In the context of increasing competition in healthcare services, marketing strategies and the quality of doctor services are two crucial aspects that can influence patient satisfaction levels. This study aims to analyze the influence of marketing strategies and doctor service quality on patient satisfaction, both partially and simultaneously. The research method used is a quantitative approach with multiple linear regression analysis. Data were collected through distributing questionnaires to patients using services at Apotek K-24 Geliting Maumere, then processed to test the hypothesis through t-tests and F-tests. The results of the study found that marketing strategies have a significant influence on patient satisfaction at Apotek K-24 Geliting Maumere. The more effective the promotion, information delivery, and approach to patients, the higher the level of satisfaction with pharmacy services. In addition, the quality of doctor services also proved to have a significant influence. Communication skills, examination accuracy, friendliness, and professionalism of doctors directly contribute to increased patient satisfaction. Further findings indicate that marketing strategies and doctor service quality simultaneously have a strong influence on patient satisfaction. A pharmacy's success in building satisfaction is determined not only by marketing efforts, but also by the quality of doctor services that create a positive patient experience. The synergy between the two increases trust, strengthens loyalty, and emphasizes that patient satisfaction requires an integrated approach that encompasses promotion, information, and quality direct interaction